Microwave-assisted extraction enhances Aquafaba functionality: A high value-added egg white replacer in vegan meringue production - Zahra Kargar; Abdollah Hematian Sourki (Food Chemistry: X)
This study aimed to compare microwave-assisted extraction (MAE) with conventional extraction methods regarding the physicochemical, techno-functional, molecular, and thermal properties of chickpea aquafaba. The potential of microwave-extracted aquafaba (MAEA) as an egg white replacer in vegan meringue production was also evaluated. The results indicated that while MAE reduced extraction yield and foam stability, it enhanced protein content, density, dry matter, and foaming ability compared to conventionally extracted aquafaba (CEA). X-ray diffraction revealed a reduction in protein crystal size, and FT-IR analysis confirmed the absence of harmful compounds in MAEA. Thermogravimetric analysis (TGA) identified key thermal degradation points. Substituting egg whites with aquafaba affected batter properties and meringue characteristics, but sensory evaluation showed no significant differences. Meringue with 50 % aquafaba substitution had the highest quality score, suggesting that this replacement offers economic and environmental benefits while meeting consumer preferences.